KONTRIBUSI AGROFORESTRI TERHADAP PENDAPATAN RUMAH TANGGA PETANI (Studi Kasus: Desa Janji Raja, Kecamatan Sitiotio, Kabupaten Samosir, Sumatera Utara) - Pebrianto Rajagukguk; Evi Sribudiani; M.Mardhiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agroforestry is a land use system which combines woody plants with agricultural crops or combines woodys. Janji Raja village became one of the villages that make agroforestry as a source of their economy. The research was conducted to provide information regarding the contribution of agroforestry to the farmer households , information about the agroforestry system adopted  as well as level efficiency of  the agroforestry system adopted by local farmers. The results of research showed that farmers implement simple agroforestry system who combined  trees with fruit crops and trees with crops in which land with agroforestry systems contribute to farmer household income was 55.24% and agroforestrysystem is considered to be very efficient with the value of an efficiencyof 13,78. Keywords: agroforestry, contribution, revenue, efficient